Quantitative Scintigraphy Evaluated the Relationship between 131I Therapy and Salivary Glands Function in DTC Patients: A Retrospective Analysis. (14th April 2022) - Lv, Xiaolan; Yin, Liang; Wu, Weiming; Li, Ning; Zhang, Ruyi; Li, Xue; Jia, Qiang; Tan, Jian; Wang, Peng; Zheng, Xiangqian; He, Xianghui; Huang, Chao; et al.
Abstract : Purpose . Quantitative scintigraphy to evaluate salivary gland function changes in patients with differentiated thyroid cancer (DTC) after iodine-131 ( 131 I) treatment. Methods . A total of 458 patients with DTC grouped by sex and age were included. Salivary gland scintigraphy was performed to evaluate salivary gland function before and after 131 I treatment. The uptake fraction (UF), uptake index (UI), and excretion fraction (EF) of two pairs of parotid glands and submandibular glands were measured and compared. The Chi-square test was conducted according to function impairment count. Results . Salivary gland function in different age groups and sexes were quite different, especially for women <55 years old, who had decreased UF, UI, and EF of all four glands without basal injury. The secretion or uptake function of some salivary glands with basic function impairment before 131 I treatment was increased after iodine treatment. Only a small percentage of males showed reduced functional parameters after several treatments. The most significant difference in the count of impairment for the four salivary glands were the first and third examinations, which was more evident in women. The submandibular gland had the most significant reduction in uptake. Conclusion . Changes in salivary gland function are more common in young females being treated for DTC. Impairment of salivary gland function is correlated with the number of treatments and the cumulative dose of 131 I. Some salivary gland functions impaired before 131 I treatment were enhanced in the early treatment.